Samantha, An American Girl Holiday [videorecording (DVD)] - Farrow, Mia, 1945-; Robb, AnnaSophia, 1993- (American Girl, Samantha., 2004)
Kindhearted Samantha Parkington's 1904 New York City world changes when Nellie O'Malley walks into her life. Nellie, her father, and two little sisters move in next door to be servants for the Ryland family. Though they come from completely different backgrounds, Samantha and Nellie become fast friends. The girls turn to each other in happiness and sorrow, adventure and danger, and grow to be as close as two sisters could ever be. But life is full of surprises and nothing prepares them for the life-altering one that lies just ahead.